BUILDING BRAND AWARENESS THROUGH CONTENT MARKETING IN THE IMPLEMENTATION OF CUSTOMER PATH 5A ON TOUR AGENT PT DOCTOR TRIP INDONESIA - Stifani Emerta Perangin-angin; Endang Sulistya Rini; Erman Munir (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Competition in the tour agent business is increasing in the digital era, especially to increase sales figures. The use of content marketing strategies is carried out to build brand awareness in the customer path process. This research aims to test the influence of brand awareness through content marketing in implementing customer path 5A at the Doctor Trip Indonesia tour agent. Doctor Trip Indonesia is a company that has only been established for 3 years. This research uses quantitative methods by conducting a survey of 190 respondents. The population in this research are consumers who have made a purchase at least once. This research uses accidental sampling with purposive sampling technique. Data collection was carried out from March to April 2024, and processed using the Structural Equation Model Partial-Least Square (SEM-PLS). The research results show that brand awareness through content marketing has a positive and significant effect on customer path 5A. It is hoped that the results of this research can be a reference for managers in determining strategies to increase the effectiveness of content marketing in building brand awareness until it reaches the final level of customer path 5A.